Early Appraisal of Option B+ In Tiko Health District- Cameroon - Tassang, Andrew; T, Nana Njamen; Assop; Thierry, Tassang; CJ, Njamen Nana; Paulette, Ngum Fru; Nchang, Cho Frederick (International Journal of Scientific Research and Management (IJSRM), 2020)
Introduction: Cameroon in 2014 had a HIV prevalence rate of 4.6 %. It is estimated that about 90% of new infections occur as a result of heterosexual relations. In 2010 in Cameroon, 7,300 babies were estimated to be born HIV positive due to mother-to-child transmission (MTCT). Faced with these realities, Cameroon has been stepping up its response steadily from Option A then B and now Option B+. To have an early appraisal of the Option B+ approach as far as the prevention of mother to child transmission of HIV (PMTCT) is concerned in the Tiko health district- Cameroon.Methodology: This cross-sectional hospital based study was carried out in Tiko from the 1st of December 2015 to the 31st of August 2016. With the use of a questionnaire, a total of 111 women whose infants underwent the polymerase chain reaction (PCR) test at six weeks were surveyed. Univariate and bivariate data analysis were performed with CDC- Epi-Info 7.2.2.6.Results: Out of 111 women included in this study, only 2 (1.8%) babies had a positive PCR test. Two cases of infected babies were realised in the study, 1 in each of the first two trimesters of pregnancy. It could probably be due to the fact that, these women got infected while they were already pregnant or maybe before their introduction to the Option B+. However, the infectious rate was similar to that of women on tritherapy. Interventions like the use of Antiretroviral (ART) drugs by infected pregnant women, safe delivery practices and safe infant feeding helped reduce the risk of transmission to infants (from 40% to 5%).Conclusion: The infection rate of 1.8 % is similar to those of women who are on tritherapy in many studies. Despite the fact that the implementation of option B+ looks more onerous, the long term benefits as far as cost effectiveness is concerned looks laudable. Thus this strategy should be adopted in resource restricted countries.